2008
DOI: 10.21608/erjm.2008.69543
|View full text |Cite
|
Sign up to set email alerts
|

Impact Resistance of Rubberized Concrete

Abstract: In the present paper, an experimental work was carried out to study the effect of ground waste tire rubber addition on the mechanical properties and impact resistance of normal strength concrete (NSC) with and without silica fume. Three different volume ratios of cnunb rubber (lo%, 20%, and 30%) were used as a partial replacement of sand. Two different sizes of cylinders were tested , under indirect tension test to study the size effect. Impact compression according to ACI Committee 544's repeated drop-weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…The elastic properties and fatigue resistance will also improve by using crumb rubber in concrete [ 18 ]. The previous research conducted by Sallam et al [ 19 ] revealed that resistance of crack under impact loading will be improved in the presence of rubber particle. Hameed and Shashikala [ 18 ] indicated that the stiffness of concrete will be increased when containing crumb rubber under cyclic loads.…”
Section: Railway Applicationsmentioning
confidence: 99%
“…The elastic properties and fatigue resistance will also improve by using crumb rubber in concrete [ 18 ]. The previous research conducted by Sallam et al [ 19 ] revealed that resistance of crack under impact loading will be improved in the presence of rubber particle. Hameed and Shashikala [ 18 ] indicated that the stiffness of concrete will be increased when containing crumb rubber under cyclic loads.…”
Section: Railway Applicationsmentioning
confidence: 99%
“…Impact energy is 2851 N.m at 0% replacement, and it linearly increases till reaching 3351 N.m at 24% replacement. Different ratios of increase in impact energy of rubberized concrete were previously reported by some researchers in the literature [3,10,[21][22]. A possible reason might be due to the ability of the tire rubber particles to allow for large deformations.…”
Section: Mass Lossmentioning
confidence: 83%
“…They outlined that over this ratio, toughness decreased as a result of the strength decrease. Sallam et al [54] studied three rubberized concrete mixes with 10%, 20% and 30% replacement of sand volume with crumb rubber. They showed that existence of small size grains of rubber in the concrete mix increased the mix resistance against crack initiation under impact load.…”
Section: Impact Resistance and Fracture Toughnessmentioning
confidence: 99%